No evidence for age-related differences in mitochondrial RNA quality in the female germline - Fiona Hartley; Arwa Alageel; Ruth Appeltant; Nicki Gray; Emmanouela Repapi; Dagan Wells; Suzannah A Williams; Joanna Poulton (Bioscientifica, 2022)
Mitochondrial quality is implicated as a contributor to declining fertility with aging. We investigated mitochondrial transcripts in oocytes and their associated cumulus cells from mice of different ages using RNA-seq. Mice aged 3 weeks, 9 weeks, and 1 year were superovulated, and 48 h later, oocyte cumulus complexes were collected by follicle puncture. We did not detect any major differences that could be attributed to aging. However, mitochondrial RNA transcripts which deviated from the consensus sequence were found at a higher frequency in cumulus cells than in their corresponding oocyte. Previous investigations have shown that variation in the sequence of mtRNA transcripts is substantial, and at least some of this can be accounted for by post-transcriptional modifications which impact base calling during sequencing. Our data would be consistent with either less post-transcriptional modification in mitochondrial RNA from oocytes than cumulus cells or with lower mtDNA mutational load.